Molecular mechanism of ribosome binding trGTPase, BipA - Goh, Kwok Jian (Nanyang Technological University, 2020)
BPI-inducible protein A (BipA), a highly conserved paralog of well-known translational GTPases LepA and EF-G, has been implicated in bacterial motility, cold shock, stress response, biofilm formation, and virulence. BipA binds in the aminoacyl- (A) site of the bacterial ribosome and establishes contacts with functionally important regions of both subunits, implying it has a physiological role in ribosome biogenesis and/or translation. When cultured at suboptimal temperatures, the E. coli bipA genomic deletion strain (ΔbipA) exhibits growth, swimming motility and ribosome assembly defects, which can be complemented by a plasmid expressing BipA, or deletion of genomic rluC. Based on the growth curve, soft agar swimming assay, and polysome profiles, His78 mutation rendered plasmid borne BipA unable to complement the genomic bipA genomic deletion phenotypes. Furthermore, C-terminal loop truncation exacerbates all phenotypes. Analysis of existing structures revealed direct interaction between BipA C-terminal loop and A-loop of 23S rRNA, suggesting its important role that is yet elucidated. Mass spectrometry analysis of ΔbipA strain proteome revealed upregulations of many proteins involved in ribosome biogenesis and RNA metabolism (e.g. DeaD, RNase R, CspA, RpoS, and ObgE), which were restored to wild-type levels by plasmid borne BipA or rluC genomic deletion, implying BipA involvement in RNA metabolism and ribosome biogenesis. The upregulated proteins in ΔbipA strain are likely compensating the loss of BipA during 50S biogenesis at low temperature. Binding assays showed that BipA cosediments with ribosome large subunit precursor (pre-50S), suggesting its role in biogenesis of ribosome large subunit. Interestingly, a direct interaction between adenine 2662 of sarcin-ricin loop and lysine 175 of r-protein L6 was observed in existing molecular structure. Such interaction was not seen when ribosome was bound by other trGTPases, supporting the idea that BipA involves in recruiting r-protein L6. All in all, BipA can be considered a bona fide ribosome assembly factor in 50S biogenesis.